Persistence in Phytopathogenic Bacteria: Do We Know Enough? - Martins, Paula M. M.; Merfa, Marcus V.; Takita, Marco A.; De Souza, Alessandra A. (Frontiers in Microbiology, 2018)
Phytopathogenic bacteria affect a wide range of crops worldwide and have a negative impact in agriculture due to their associated economic losses and environmental impacts. Together with other biotic and abiotic stress factors, they pose a threat to global food production. Therefore, understanding bacterial survival strategies is an essential step towards the development of new strategies to control plant diseases. One mechanism used by bacteria to survive under stress conditions is the formation of persister cells. Persisters are a small fraction of phenotypic variants within an isogenic population that exhibits multidrug tolerance without undergoing genetic changes. They are dormant cells that survive treatment with antimicrobials by inactivating the metabolic functions that are disrupted by these compounds. They are thus responsible for the recalcitrance of many human diseases, and in the same way, they are thought to contribute to the survival of bacterial phytopathogens under a range of stresses they face in the environment. It is believed that persister cells of bacterial phytopathogens may lead to the reoccurrence of disease by recovering growth and recolonizing the host plant after the end of stress. However, compared to human pathogens, little is known about persister cells in phytopathogens, especially about their genetic regulation. In this review, we describe the overall knowledge on persister cells and their regulation in bacterial phytopathogens, focusing on their ability to survive stress conditions, to recover from dormancy and to maintain virulence.